ANTIFERTILITY EFFECTS OF POUZOLZIA MIXTA IN FEMALE WISTAR RATS - Sewani-Rusike, Constance Rufaro (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The continued use of plants by women to prevent pregnancy suggests there are plants out there with potential use as contraceptives. In Zimbabwe, Pouzolzia mixta is used as a “morning after” contraceptive, thus it may possess postcoital antifertility activity. To test contraceptive activity, animals (n=8/group) were orally pretreated with aqueous (EqPM) or ethanolic (AtPM) extract of P. mixta at 300mg/kg b.wt for 7 days followed by mating with continued treatment for 10 days post-conception. To test for postcoital activity, treatment was initiated on day-1 of pregnancy and continued for 10 days. Laparotomy was performed and implantations counted. For estrogenic activity, immature ovariectomised rats were treated for 7 days after which vaginal opening and uterine weights were determined. In vitro oxytocic effects were performed using uterine tissue in organ bath with De Jalon’s solution. Acetylcholine (Ach) was the positive control. Results showed modest contraceptive activity with EtPM more effective in inhibiting fertility compared to AqPM (25% vs 37.5%) with a similar trend for antiimplantation effects (31% vs 19%). There was potent postcoital antifertility effects with AqPM more effective in inhibiting implantation (94.6% vs 86%) and fertility (87.5% vs 75%) compared to EtPM. Immature rat bioassay for estrogenic activity demonstrated pronounced estrogenic activity by both extracts. Oxytocic effects at 400ng/ml were more pronounced for the AqPM (92% of 100ng/ml Ach) than EtPM (25% of 100ng/ml Ach). Findings demonstrate the antifertility effects of aqueous and ethanolic extracts of P. mixta. The antifertility effects may be attributed to antiimplantation, estrogenic and oxytocic effects of the plant extracts.